(untitled) (Scientific journal of the Fergana State University, 2024)
In our study, pragmatic relations in fiction translation were considered on the same level as semantic relations, analysis of the source text and creation of an equivalent text in the target language. The pragmatics of translation is focused on the communication between the speaker and the listener, and the participants of the conversation belong to certain cultural and national groups. The cultural and national features of the interlocutors were analyzed. The influence of extra-linguistic factors on the translation process, i.e. reflecting the features of the text, its lexical content and main idea in such a way as to convey its communicative orientation to the recipient taking into account the pragmatic possibilities of the text. and how this aspect is translated has been reasonably shown.